Evaluating online resources in terms of learning environment and student attitudes in middle-grade mathematics classes - Earle, James E.; Fraser, Barry (Springer, 2016)
The main objective of this research was to use learning environment and attitude scales in evaluating online resource materials for supporting a traditional mathematics curriculum. The sample consisted of 914 middle-school students in 49 classes. A second research focus was the validation of the chosen learning environment questionnaire, the Technology-Rich Outcomes-Focused Learning Environment Inventory (TROFLEI), with an ethnically-diverse sample of middle-grade mathematics students in Florida. Finally, we complemented quantitative questionnaire data with qualitative interview data that were analysed thematically. In addition to cross-validating the TROFLEI, our study suggested that the online resource provided neither much advantage nor much disadvantage. © 2016 Springer Science+Business Media Dordrecht